Numerical simulation of initial pressure effect on energy input in spark discharge in nitrogen - Korytchenko, K.V.; Tomashevskyi, R.S.; Varshamova, I.S.; Dubinin, D.P.; Lisnyak, A.A.; Lipovyi, V.O. (Вопросы атомной науки и техники, 2019)
An influence of initial gas pressure on energy deposited by spark discharge in nitrogen during the spark channel expansion is evaluated. Influence of the pressure on efficiency of energy deposition and emitted energy in a discharge channel is simulated. Dependencies of dynamic of energy input and an energy correlation coefficient on the pressure are found out. It was suggested to use an average value of the correlation coefficient to model a load of spark channel by the any initial pressure when a spark load is formed by atmospheric conditions. Досліджено вплив початкового тиску газу на енергію, що виділяється іскровим розрядом в азоті при розширенні іскрового каналу. Розраховано вплив тиску на ефективність введення і випромінювання енергії в каналі розряду. Виявлено залежності динаміки енергоуводу і коефіцієнта енергетичної кореляції від тиску. Запропоновано використовувати середнє значення коефіцієнта кореляції для моделювання навантаження іскрового каналу при будь-якому початковому тиску на іскровому навантаженні в атмосфері. Исследовано влияние начального давления газа на энергию, выделяемую искровым разрядом в азоте при расширении искрового канала. Рассчитано влияние давления на эффективность введения и излучения энергии в канале разряда. Выявлены зависимости динамики энерговвода и коэффициента энергетической корреляции от давления. Предложено использовать среднее значение коэффициента корреляции для моделирования нагрузки искрового канала при любом начальном давлении на искровой нагрузке в атмосфере.